ANALYSIS OF AUTODESK INVENTOR E-MODULE IMPLEMENTATION IN ENGINEERING DRAWING SUBJECT (CASE STUDY AT SMKS ALKHAIRAAT BAHODOPI VOCATIONAL HIGH SCHOOL MOROWALI) - Darmono Darmono; Rizal Justian Setiawan; Khakam Ma'ruf; Mahda Enja Al Hudha; Nur Evirda Khosyiati (STKIP Persada Khatulistiwa Sintang, 2024)
Learning media is very necessary in the learning process in vocational high schools. The development and use of e-modules is one effort to increase students' understanding of lessons. This research used experimental methods and was conducted at Alkhairaat Bahodopi Vocational High School in the 2023/2024 academic year. The sample selection was class XI TP 1 with 10 students as the control class and class XI TP 2 with 10 students as the experimental class. The design of this research is Pretest-Posttest Control Group Design. The research instrument is student learning outcomes. Hypothesis testing uses the paired sample t-test. The analysis was carried out descriptively. The research results show that the use of E-Modules affects increasing student learning achievement compared to learning without E-Modules. This is proven by the sig value < 0.001 for both knowledge and skills values in the experimental class, which shows that the sig value is smaller than Î± = 0.05, so H0 is rejected and Ha is accepted. The implementation of learning with Autodesk Inventor e-modules in class XI TP 2 made a positive contribution in improving students' academic achievement, especially when compared to the usual learning in the classroom.